The Effect of a 12-Minute Aerobic Running Program on the Endurance of Adolescent Football Players at Bhatara Football School Sumedang - Audy Auzora Mustafa; Adang Sudrazat; Rizal Ahmad Fauzi (Journal Coaching Education Sports, 2026)
This study aimed to determine the effect of a 12-minute aerobic exercise program on improving the aerobic endurance of adolescent football students at SSB Bhatara Sumedang. The study employed an experimental method using a one-group pretest-posttest design. The research sample consisted of 30 adolescent football students. The Cooper Test was used as the research instrument to measure participants’ aerobic endurance. The training program was conducted over 10 sessions. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired sample t-test. The results showed an increase in the average endurance score from 37.33 in the pretest to 77.33 in the posttest. The hypothesis test results indicated a significance value of 0.000 < 0.05, meaning that the 12-minute aerobic exercise program had a significant effect on improving the aerobic endurance of adolescent football students. Therefore, the 12-minute aerobic exercise program can be considered an effective alternative physical training method in youth football development.